2022
DOI: 10.1371/journal.pone.0270769
|View full text |Cite
|
Sign up to set email alerts
|

Elevational distribution of montane Afrotropical butterflies is influenced by seasonality and habitat structure

Abstract: Determinants of elevational distribution of butterfly species richness and abundance in the tropics are poorly understood. Here we assess the combined effects, both additive and interactive, of seasonality and habitat structure on the elevational distribution of butterflies in the Uluguru Mountains, Tanzania. We sampled butterflies along a 1100 m elevational gradient that extended from 1540 to 2639 m using a time-constrained fixed-area method during the short to long rains and long to short rains transitions, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 57 publications
1
0
0
Order By: Relevance
“…In addition, only two individuals of Papilionidae family were sampled only in grassland and riverine forest (Tables 2 and 3). Tis fnding is consistent with the results of the authors of [51,64] who reported that the group members of the Hesperiidae and Papilionidae families were least represented in their research studies in the country. Te low family abundance Hesperiidae and Papilionidae that was observed in grassland, Miombo woodland, and riverine forest may be attributed to the type of habitat and host plant availability as butterfy species richness and abundance are linked to the host specifcity and niche preferences [65].…”
Section: Discussionsupporting
confidence: 90%
“…In addition, only two individuals of Papilionidae family were sampled only in grassland and riverine forest (Tables 2 and 3). Tis fnding is consistent with the results of the authors of [51,64] who reported that the group members of the Hesperiidae and Papilionidae families were least represented in their research studies in the country. Te low family abundance Hesperiidae and Papilionidae that was observed in grassland, Miombo woodland, and riverine forest may be attributed to the type of habitat and host plant availability as butterfy species richness and abundance are linked to the host specifcity and niche preferences [65].…”
Section: Discussionsupporting
confidence: 90%